Pola Perilaku Penelusuran Informasi Mahasiswa Prodi Ilmu Perpustakaan UINSU di Era Digital Native - Rahayu, Sri; Mahendra, Dinda Salsabilla; Ummi, Nurul; Purwaningtyas, Franindya (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information search behavior is an attitude or action in seeking or finding the information needed. Information search behavior is important to do to get the required information that can help in solving problems. Kriklas (2006: 16), argues that information seeking behavior is an activity in determining and identifying messages to satisfy perceived information needs. The method used in this research is a qualitative research method to describe the nature of the problems being monitored. Sulistyo-Basuki (2006: 78) describes qualitative research intending to get a complete reflection of things for the thoughts of people being watched. This research results that in the search for information, it is included in the novice category. Because according to Hsieh Yee, a novice information seeker is a non-professional searcher who has no experience in searching or has never attended college or practiced online searching. Keywords: Pattern, Information Searching Behavior, Digital Native